2021
DOI: 10.1016/j.xcrm.2021.100424
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic evaluation of metabolic alterations in multiple sclerosis identifies shifts in aromatic amino acid metabolism

Abstract: Highlights d Significant alterations in the circulating metabolome are noted in multiple sclerosis d Aromatic amino acid (AAA) metabolite levels are linked to disease severity d Expression of AAA metabolism genes is altered in MS blood and CSF immune cells d AAA metabolites alter human monocyte cytokine production and endocytosis

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 68 publications
5
26
1
Order By: Relevance
“…Among all DAMs, the most significant alterations were observed in the levels of amino acid metabolites; for instance, the relative levels of beta-alanyl-Larginine, L-glutamic acid, and L-valine were significantly increased, whereas those of L-tryptophan, L-leucine, L-isoleucine, L-tyrosine, L-phenylalanine, and cis-4-hydroxy-D-proline were significantly reduced in MS-affected patients compared with those in healthy subjects. Independent studies also showed similar changes in amino acid profiles in MSaffected subjects (102,103). The upregulation in the levels of L-glutamic acid and the downregulation in the levels of L-leucine and L-isoleucine were consistent with the results of previous studies (26,44).…”
Section: Discussionsupporting
confidence: 87%
“…Among all DAMs, the most significant alterations were observed in the levels of amino acid metabolites; for instance, the relative levels of beta-alanyl-Larginine, L-glutamic acid, and L-valine were significantly increased, whereas those of L-tryptophan, L-leucine, L-isoleucine, L-tyrosine, L-phenylalanine, and cis-4-hydroxy-D-proline were significantly reduced in MS-affected patients compared with those in healthy subjects. Independent studies also showed similar changes in amino acid profiles in MSaffected subjects (102,103). The upregulation in the levels of L-glutamic acid and the downregulation in the levels of L-leucine and L-isoleucine were consistent with the results of previous studies (26,44).…”
Section: Discussionsupporting
confidence: 87%
“…Recently, Fitzgerald et al identified abnormalities in aromatic amino acid (AAA) metabolites using a multi-omic approach in patients with MS. A reduced quantity of AAA metabolites correlated with higher disability, and altered AAA metabolism was found in CSF- and serum-derived monocytes of patients with MS. These AAA metabolites may come from the gut microbiota 154 . Levels of butyrate- or indolelactate-producing bacteria are reduced in patients with MS 155 .…”
Section: Is Multiple Sclerosis a Metabolic Disease?mentioning
confidence: 99%
“…Modulating the metabolism of the AAA tryptophan, which is reduced in the serum and CSF of patients with MS 154 , 164 , 165 , could have therapeutic value. In vivo models showed reduced levels of tryptophan metabolites on both sides of the BBB (cortex and serum) during demyelination 166 .…”
Section: Is Multiple Sclerosis a Metabolic Disease?mentioning
confidence: 99%
See 1 more Smart Citation
“…Studying metabolites in biofluids during disease states is emerging as a powerful approach, as distinct metabolite signature could be a potential biomarker for disease progression or predictive of the beneficial effect of DMTs in MS [ 154 ]. Few studies have outlined a distinct metabolic signature, including serum phospholipids [ 155 ], altered bile acid metabolism [ 156 ], abnormalities in aromatic amino acid metabolism [ 157 ], and pro-resolving lipid mediators in MS compared to healthy subjects, which could be developed as a biomarker for disease and/or novel therapy. Moreover, altered metabolite signature during disease relapse [ 158 , 159 ] could be developed as a metabolic biomarker for disease progression in MS.…”
Section: Biomarkers For a Future Bioinformatic Approachmentioning
confidence: 99%